The 10 Year Course of AA Participation and Long-Term Outcomes: A Follow-up Study of Outpatient Subjects in Project MATCH - Pagano, Maria E. (2013)
This study investigates the 10-year course and impact of AA-related helping (AAH), step-work, and meeting attendance on long-term outcomes. Data were derived from 226 treatment-seeking alcoholics recruited from an outpatient site in Project MATCH and followed for 10 years post-treatment. Alcohol consumption, AA participation, and other-oriented behavior were assessed at baseline, end of the 3-month treatment period, and one year, three years, and 10 years post-treatment. Controlling for explanatory baseline and time-varying variables, results showed significant direct effects of AAH and meeting attendance on reduced alcohol outcomes and a direct effect of AAH on improved other-oriented interest.